Sistem Informasi Penentuan Kelompok Belajar Siswa SMK Negeri 2 Bandung Menggunakan Algoritma K-Means - Hidayatulloh, Syarif (JURNAL TEKNIK INFORMATIKA, 2021)
Vocational High School (SMK) is a vocational secondary education level in formal education in Indonesia. Based on the 2003 National Education System Law concerning the objectives of secondary education, vocational students are prepared to enter the world of industry or the world of work. SMK students can choose one of the several majors available at of semester 2 of class X. The purpose of the majors is to help prepare students to continue their studies and choose the world of work so that they can help strengthen success and suitability for future achievements. Study groups are formed according to the abilities and suitability of students in their respective fields. The essence of the study groups is learning from each other where students can share knowledge and insights between students in a group. Therefore, it is necessary to develop a student learning grouping system based on certain criteria using clustering techniques. The clustering method is a method that will classify a number of data into groups so that each group contains data that is as similar as possible. The purpose of this clustering is to minimize the variation of members within one cluster and maximize member variation between clusters.